Representasi substantif Organisasi PEREMPUAN AMAN di Sumatera Utara dan Nusa Tenggara Timur - Dian Ratna Sari; Nur Iman Subono; Kurniawati Hastuti Dewi (Jurnal Inada: Kajian Perempuan Indonesia di Daerah Tertinggal, Terdepan, dan Terluar, 2022)
This article analyzes substantive representation of PEREMPUAN AMAN organization. This paper fills the gap as the existing research only analyzes women's organizations at the level of descriptive representation. By exploring substantive representation of PEREMPUAN AMAN, this paper reveal contribution of PEREMPUAN AMAN in increasing the capacity of indigenous women in their organizing area. The qualitative approach and feminist research methodology used in this study to capture the experiences of indigenous women members of the PEREMPUAN AMAN Community Daily Management (PHKom) Menteng, Deli Serdang, North Sumatra and Community Daily Management (PHKom) Kompetar, Nagekeo, East Nusa Tenggara. These two locations were chosen to represent the 3T (Outermost, Frontier, Disadvantaged) region. The finding shows that PEREMPUAN AMAN has succeeded in bringing their organization to the level of substantive representation. The substantial work carried out by PEREMPUAN AMAN in the organizing area of ​​PHKom Menteng and PHKom Kompetar has succeeded in increasing the capacity of indigenous women individually and collectively: 1) indigenous women learn to organize themselves to fight for their rights, 2) indigenous women braved to voice their opinions during the lobbying process with the Local House of Representative and the regent, 3) indigenous women eager to run as candidates for legislative members, hamlet heads and Village Consultative Bodies (BPD), despite encountering obstacles, and 4) indigenous women became the driving force of their community by conducting various social works.